2020
DOI: 10.1371/journal.pone.0220482
|View full text |Cite
|
Sign up to set email alerts
|

Feeding intensity and molecular prey identification of the common long-armed octopus, Octopus minor (Mollusca: Octopodidae) in the wild

Abstract: The common long-armed octopus, Octopus minor

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…A similar situation has been reported for immature O. mimus in China that experiences high feeding intensity in April and June (Bo et al, 2020). This is probably because each octopus species experiences different feeding patterns depending on the period of availability and prey abundance in a particular geographical location.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…A similar situation has been reported for immature O. mimus in China that experiences high feeding intensity in April and June (Bo et al, 2020). This is probably because each octopus species experiences different feeding patterns depending on the period of availability and prey abundance in a particular geographical location.…”
Section: Discussionsupporting
confidence: 79%
“…For example, Quetglas et al (2005) observed a high incidence of empty stomachs in ripe O. salutii, while Bo et al (2020) noticed the presence of more than half of adult O. minor females with empty stomachs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stomach contents exhibit prey compositions that differ markedly from midden counts for shelled mollusks and soft-bodied organisms, and flaws in prey identification have been identified for both methods (Smith, 2003). Rapid digestion and external ingestion can make the stomach contents visually unidentifiable (e.g., Bo et al, 2019). Midden contents left around dens after the GPO processes prey are often highly fragmented, making accurate identification difficult (Boyle and Rodhouse, 2005).…”
Section: Introductionmentioning
confidence: 99%